Analisis UU ITE dan Perlindungan Data Pribadi: Implikasi Tanggung Jawab Pidana dalam Kasus Doxing pada Pemilu 2024. - I Gusti Ayu Pramesti Gayatri Devi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The general election as a pillar of democracy faces new challenges with the rapid development of information technology, one of which is the practice of doxing—disseminating personal data without consent to harm individuals. In the context of Indonesia’s 2024 General Election, doxing cases have increased, targeting political figures and ordinary citizens, potentially undermining political participation and violating the right to privacy. This study aims to analyze the legal framework governing doxing based on Law Number 1 of 2024 concerning Electronic Information and Transactions (ITE Law) and Law Number 27 of 2022 concerning Personal Data Protection (PDP Law), as well as to examine the form of criminal liability for perpetrators of doxing in the context of the 2024 election. This normative juridical research employs statutory, conceptual, and case approaches. The findings reveal that although not explicitly regulated, doxing can be classified as a legal violation under the two laws. However, law enforcement still faces technical and normative obstacles, such as difficulty in identifying perpetrators and proving intent. Strengthening legal provisions and the capacity of law enforcement officers is essential to ensure accountability without compromising democratic principles.